The Effect of Plyometric and Balance Training Methods on 100 Metres Running Ability in Junior High School Students State 2 Bitung - Riwi Alviolita Tanod; Nolfie Piri; Jan Lengkong (International Journal of Public Health, 2024)
The purpose of this study was to determine: (1) The difference in the effect of plyometric training methods between double leg bound training and double leg vertical power jump training on 100-meter running ability, (2) The difference in the effect between high balance and low balance on 100-meter running ability, (3) Interaction between plyometric and balance training methods on 100-meter running ability. The instruments used to collect data were: (1) Balance test (Modified Bass Test of Dynamic Balance), (2) 100-meter running ability test with time test, (3) Training program as a guideline that will be used in providing treatment . The data analysis technique used was Analysis of Variance (ANOVA) at a significance level of α = 0.05. The results of the hypothesis testing proved that: (1) There is no difference in the influence between double leg bound training and double leg vertical power jump training on 100-meter running ability. By looking at the similarity of the movements that both jump use both legs, it seems that these two exercises are variations in training, as a result the two plyometric training methods are not significantly different. (2) There is a difference in the influence between high balance and low balance on 100-meter running ability. The results of the data analysis showed that high balance has a significant difference in influence with low balance. (3) There is no interaction of influence between plyometric and balance training methods on 100-meter running ability. Related to the interaction hypothesis, it turns out that the results of the hypothesis testing have proven that there is no interaction between plyometric and balance training methods on 100-meter running ability where the calculated F value = 0.006 < than the F table value = 2.82 at a significance level of α = 0.05. Conclusion of the study: 1) There is no significant difference in influence between double leg bound training and double leg vertical power jump training on 100-meter running ability. 2) There is a significant difference in the influence of high balance and low balance on 100-meter running ability. 3) There is no interaction between plyometric training methods and balance on 100-meter running ability.